Magnetic domain states in nano-sized Co nuclei electrodeposited onto monocrystalline silicon - Moina, C. A.; De Oliveira-Versic, L. [UNESP]; Vazdar, M. (Elsevier, 2004)
In the present work, nano-sized magnetic nuclei of Co have been electrodeposited onto p-Si (111). The deposition follows a mechanism of progressive nucleation and growth controlled by diffusion. MFM studies showed that the transition between magnetic domain states is strongly dependent on the size and shape of the nuclei. A critical height h0 is defined below which the nuclei presented always a single-domain configuration. The limiting lower boundary for the single-domain state calculated from the theory is quantitatively coincident with the experimental results. © 2004 Elsevier B.V. All rights reserved.
Keywords: AFM/MFM; Co electro-deposition; Electrochemical nucleation; Magnetic materials; Nanomaterials; Atomic force microscopy; Electrochemistry; Electrodeposition; Nanostructured materials; pH effects; Physical vapor deposition; Semiconductor materials; Silicon; Sputtering; Co electrodeposition; Magnetic force microscopy (MFM); Crystalline materials